Neutrophil Extracellular Traps as Potential Therapeutic Targets in Systemic Lupus Erythematosus: A Systematic Review of Current Evidence - Primartati, Danny Meganingdyah; Fatmariza, Aulia Risqi; Darmawan, Rahmad; Fadillah, Noor (Fakultas Sains, Teknologi, dan Analsisi Institut ilmu Kesehatan Bhakti Wiyata, 2025)
Introduction: Systemic Lupus Erythematosus is an autoimmune disorder in which the immune system becomes increasingly dysregulated, inflamed, and involves multiple organ systems. While NETs play an essential role in antimicrobial defence, in SLE, they enhance immunopathological damage by driving type I interferon response, autoantibody production, and tissue damage. NETs, due to their unique capability of serving both as disease extraditional and as disease instigators, are a promising target in SLE. Methods: The current review is in accordance with PRISMA guidelines and registered in PROSPERO (CRD420251129386). Comprehensive searches were performed in PubMed, ScienceDirect, SpringerLink, and JSTOR, published between 2021 and 2025. Primary research investigating NETs or interventions aimed at them in SLE were included. Articles were excluded for non-originality, focus outside SLE and NETs, and lack of therapeutic focus. Documents were appraised for design, population, sample size, intervention, outcome, and therapeutic relevance for extraction. Results: A total of 1.065 articles were initially identified, of which six studies met inclusion criteria. Clinical studies consistently demonstrated elevated NET remnants, impaired NET degradation, and organ-specific deposition associated with lupus nephritis and vascular involvement. Preclinical models showed that PAD4 inhibition, DNase I supplementation, and mitochondrial-targeted antioxidants reduced NET formation, attenuated interferon-driven immune responses, and ameliorated renal and vascular pathology. Conclusion: Existing data underscore the role of NETs as critical pathogenic components of SLE and corroborate the possibility of NETs as therapeutic targets. There is, however, an immediate need for bespoke NET assays, active-signed NET biomarker stratification, NET-guided patient stratification, and rigorous clinical trial design.